Discipline and Responsibility of Certified Teachers in Elementary School’s Social Science - Halimatus Sakdiah; Rahmi Rahmi; Ismi Della Hakiki; Lidya Oktavia Putri; Widya Pratama Sri Putri; Khusnul Aulia Rahmi; Safrudin Safrudin (International Journal Labs, 2022)
This study aims to: Determine the implementation of the Integrated Social Studies learning model in SD Negeri 0708 Aliaga II, identify the inhibiting factors, and find out the efforts made by social studies teachers in increasing professionalism. This research is an evaluation study using a qualitative descriptive research method. This form of research tends to use a single case study. The research subjects were Social Studies teachers at SD Negeri 0708 Aliaga II. Techniques and data collection tools used, namely: interviews, observations, and recording archives and documents. The results showed that: In the implementation of Integrated Social Studies learning at SD Negeri 0708 Aliaga II there were still many differences. There are those who carry out Integrated Social Studies learning in full, semi-integrated, and unintegrated. The obstacles faced, among others: lack of understanding or mastery of the material outside the field, lack of knowledge and understanding of Integrated Social Studies learning models, difficulties in applying the concept of Integrated Social Studies learning, and skepticism from social studies teachers themselves. The efforts made by social studies teachers in improving their professional competence, among others: Asking other social studies teachers, reading reference books on social studies, attending training, socialization, seminars, and various (sharing) experiences.